Report of the wintering party of the 45th Japanese Antarctic Research Expedition, 2004-2005 -Activities at Syowa Station and the coastal area- - Hisao Yamagishi (National Institute of Polar Research, 2006)
The 45th Japanese Antarctic Research Expedition (JARE-45) wintering party, consisting of 40 members and 2 journalists, conducted the third year program of the VIth five-year plan of JARE at Syowa Station and inland Dome Fuji Station. The program included observations in meteorology, upper atmosphere physics, atmospheric sciences, glaciology, geophysics, biology and medical science, as well as logistic activities to support the observations and maintain the station from February 1, 2004 to January 31, 2005. An Intersat satellite station was installed at Syowa Station in this expedition and started various sevices such as data transfer, internet and TV conference system. Due to the unstable sea ice condition around Syowa Station and Ongul Strait, the start of the field activities on sea ice was delayed until early July. However, many teams were engaged in field work in biology, geophysics and atmospheric sciences in the coastal area of east Lutzow-Holm Bay, as well as aeroplane observations. Two journalists at Syowa Station reported on the nature of Antarctica and various activities of the expedition.